Pengaruh Budaya Organisasi dan Motivasi Berorganisasi terhadap Komitmen Organisasi Anggota LPM Profesi Universitas Negeri Makassar - Arimayanti, Angnis; Haeruddin, M. Ikhwan Maulana; Musa, Muh. Ichwan; Kurniawan, Agung Widhi (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of organizational culture and organizational motivation on organizational commitment among active members of LPM Profesi Universitas Negeri Makassar for the 2025/2026 period. Organizational commitment is an important factor in determining the sustainability and effectiveness of student organizations. However, in practice, several organizational problems such as low participation, declining member retention, and limited engagement in organizational activities indicate that the level of commitment among members may vary. Therefore, examining the factors that influence organizational commitment becomes essential. This research employed a quantitative approach with a descriptive research design. The population consisted of all active members of LPM Profesi Universitas Negeri Makassar for the 2025/2026 period. The sampling technique used was saturated sampling, where all members of the population were included as respondents, totaling 55 participants. Data were collected through questionnaires and observations. The data analysis technique used in this study was multiple linear regression analysis using SPSS to examine the influence of organizational culture and organizational motivation on organizational commitment. The results indicate that organizational culture does not have a significant partial effect on organizational commitment, while organizational motivation shows a significant influence. However, organizational culture and organizational motivation simultaneously have a positive and significant effect on organizational commitment. These findings suggest that motivation plays a stronger role in encouraging members to remain active and committed to organizational activities, while organizational culture functions as a supporting framework that shapes organizational values and behaviors.